Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1073/pnas.1520829113
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in an intense competition for iron: Key component of the Campylobacter jejuni iron uptake system scavenges enterobactin hydrolysis product

Abstract: To acquire essential Fe(III), bacteria produce and secrete siderophores with high affinity and selectivity for Fe(III) to mediate its uptake into the cell. Here, we show that the periplasmic binding protein CeuE of Campylobacter jejuni, which was previously thought to bind the Fe(III) complex of the hexadentate siderophore enterobactin (Kd ∼ 0.4 ± 0.1 µM), preferentially binds the Fe(III) complex of the tetradentate enterobactin hydrolysis product bis(2,3-dihydroxybenzoyl-l-Ser) (H5-bisDHBS) (Kd = 10.1 ± 3.8 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 57 publications
(57 reference statements)
1
62
0
2
Order By: Relevance
“…Fluorescence quenching studies with CeuE were carried out on a Hitachi F-4500 fluorescence spectrophotometer as previously reported22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quenching studies with CeuE were carried out on a Hitachi F-4500 fluorescence spectrophotometer as previously reported22.…”
Section: Methodsmentioning
confidence: 99%
“…The octahedral coordination of the Fe(III) ion was completed by two protein residues, Tyr288 and His227. Subsequent studies22 showed that 4-LICAM 4− was a good mimic of the natural tetradentate linear enterobactin hydrolysis product: bis(2,3-dihydroxybenzoyl-L-Ser) ( PDB ID: 5ADV, 5ADW ), (Fig. 1).…”
mentioning
confidence: 99%
“…Wettkampf um Eisen 3.4.1. [75] Dieser Ansatz unterscheidet sich deutlich von der üblicheren Fe 3+ -Aufnahme durch sechszähnige Siderophore. So wurden bei der Untersuchung von cokultivierten Umweltbakterien Isolate entdeckt, deren Wachstum vollständig von benachbarten Bakterien abhängig war.…”
Section: Angewandte Chemieunclassified
“…Strukturelle und biophysikalische Studien an Campylobacter jejuni,e inem Organismus,d er keine eigenen Siderophore bilden kann, zeigten, wie CeuE, ein periplasmatisches Siderophor-Bindeprotein, von anderen Bakterien erzeugte Enterobactin-Hydrolyseprodukte mit hoher Affinitätbinden kann. [75] Dieser Ansatz unterscheidet sich deutlich von der üblicheren Fe 3+ -Aufnahme durch sechszähnige Siderophore.…”
Section: Angewandte Chemieunclassified
“…Competition for resources is the key to 85 success within the gut. Campylobacter is known to be an effective coloniser [22], as it is 86 very effective at drawing zinc [23] and iron [24] from its environment. The second term 87 (γCP ) in equation (1) models the inhibitory effect of host defence peptides, P .…”
mentioning
confidence: 99%